2019 14th IEEE International Conference on Automatic Face &Amp; Gesture Recognition (FG 2019) 2019
DOI: 10.1109/fg.2019.8756567
|View full text |Cite
|
Sign up to set email alerts
|

Shallow Triple Stream Three-dimensional CNN (STSTNet) for Micro-expression Recognition

Abstract: In the recent year, state-of-the-art for facial microexpression recognition have been significantly advanced by deep neural networks. The robustness of deep learning has yielded promising performance beyond that of traditional handcrafted approaches. Most works in literature emphasized on increasing the depth of networks and employing highly complex objective functions to learn more features. In this paper, we design a Shallow Triple Stream Three-dimensional CNN (STSTNet) that is computationally light whilst c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
172
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(172 citation statements)
references
References 32 publications
0
172
0
Order By: Relevance
“…Kim et al [64] proposed to combine CNN with long-term memory (LSTM) and remarkable results are obtained. It has been demonstrated that shallow CNN architectures are practically workable in the ME recognition system [65,66,67,68] . Overall, although the transfer learning [69] and data augmentation [70] are performed, the limited number and imbalance emotion class distribution issues pose a great challenge to develop robust feature extractors.…”
Section: Feature Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kim et al [64] proposed to combine CNN with long-term memory (LSTM) and remarkable results are obtained. It has been demonstrated that shallow CNN architectures are practically workable in the ME recognition system [65,66,67,68] . Overall, although the transfer learning [69] and data augmentation [70] are performed, the limited number and imbalance emotion class distribution issues pose a great challenge to develop robust feature extractors.…”
Section: Feature Extractionmentioning
confidence: 99%
“…Compared to other classifiers such as Random Forest (RF) [72], sparse representation classifier (SRC) [73] and Relaxed K-SVD [74], SVM appears to be more consistent across all the databases with distinct features extracted. Due to the emergence of deep learning, the Softmax classifier, normally served as the final fully connected layer, has been employed in the recent works [64,75,67,66]. Its outstanding discriminative characteristics is beneficial, especially in dealing the high-level features.…”
Section: Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The classification step is done by an FCL. An improved solution of Off-ApexNet is STSTNet [8], authors have added to the horizontal and vertical OF the strain OF to get a better result. Xia et al [9] have proposed a Spatiotemporal Recurrent Convolution Network (STRCN).…”
Section: Hybrid Approachmentioning
confidence: 99%
“…The most commonly used solutions in the state-of-the-art is the hybrid solutions [7,8,9,10]. The primary concept is to use handcrafted solution such as Local Binary Pattern on Three Orthogonal Planes (LBP-TOP) or OF to assist Convolutional Neural Network (CNN) and Recurrent Neural Network (RNN) to extract the most significant spatio-temporal features despite the database issues.…”
Section: Introductionmentioning
confidence: 99%